Safety and efficacy of infliximab and corticosteroid therapy in checkpoint inhibitor‐induced colitis. Issue 9 (19th September 2022) - Dahl, Emilie Kristine; Abed, Osama Karim; Kjeldsen, Jens; Donia, Marco; Svane, Inge Marie; Dige, Anders; Agnholt, Jørgen Steen; Bjerrum, Jacob Tveiten; Seidelin, Jakob Benedict
Summary: Background: Cancer patients treated with immune check point inhibitors are at risk of developing severe colitis. However, the efficacy and safety of treatment of severe colitis is poorly understood. Aims: To explore the safety and efficacy of infliximab and corticosteroids in severe immune‐mediated enterocolitis (IMC) Method: We performed a nationwide retrospective cohort study on 140 cancer patients treated with infliximab due to IMC in Denmark from 2011 to 2021. Results: The rate of complete remission with infliximab was 52% after one dose, increasing to 73% after two or more doses. Thirteen patients (10%) required additional treatment with vedolizumab. Patients were heavily exposed to corticosteroids and received a median accumulated dose of 3978 mg (interquartile range [IQR] 2552–6414). Age‐ and cancer‐adjusted Cox regression analysis found that a high dose of prednisolone at start of tapering ≥75 mg/day was associated with increased mortality (HR 1.67, 1.04–2.69, p  = 0.035). Patients responding to infliximab experienced an improvement of symptoms after 3 days (IQR 2–4) and complete remission after 31 days (IQR 14–61). Twenty‐four percent required hospitalisation for infection during treatment for IMC, lasting 7 days (median). Secondary gastrointestinal infections occurred in 16%, with Clostridioides difficile being most common (64%). Further, 10% had a thromboembolic event during the first 90 days after infliximab treatment. Conclusions: Infliximab led to complete resolution of symptoms in 73% of patients with IMC. High prednisolone dose at tapering was associated with increased mortality rate and a high incidence of infections and hospitalisations in patients with severe IMC. We suggest optimised infliximab treatment before escalation of steroid doses. Abstract : In this retrospective cohort, we show that a high dose of tablet prednisolone at start tapering after infliximab infusion may have an impact on survival, however patients with checkpoint inhibitor induced colitis were still expected to live longer than patients exposed to check point inhibitors without acquiring colitis (controls). Safety data shows that patients in combined immunosuppression with infliximab and steroids had a high risk of severe infections and thrombosis.